Bilan des études méthodologiques 2007 pour le projet d'analyse des risques de mortalité d'huîtres en baie de Quiberon - Fleury, Pierre-gildas; Bouget, Jean-francois; Langlade, Aime; Mazurie, Joseph; Philippon, Xavier (2008)
(subtidal on-bottom rearings), has been the year of the gestation for the RISCO-QB project (Risks in shellfish farming, in baie de Quiberon). Discussions with various potential partners have resulted in the project drafting with 3 main objectives : - estimation of the trophic capacity of the bay and adjustment of the rearing biomass, - impact of sediment nearness upon on-bottom technique and adjustment of the rearing practices, - appraisal of the impact of these 2 factors (trophic capacity and sediment nearness) on the budget of the farming companies and their consequences in the management of the mortality risk. Concurrently with the project writing, pre-studies, mainly methodological, have been conducted in the bay since 2007 in order to investigate the specific methodologies required by the subtidal on-bottom rearing technique and to provide basic data to the several-years study (2008-2012) of the RISCO-QB project : - Sampling of sediment (Nov. 2007) for granulometric and chemical (organic matter) analysis, - Physical and phytoplanctonical monitoring, in situ (probes), - Potential use of spatail remote detection for the seawater monitoring, - Comparative monitoring of mortality and growth of on-bottom and off-bottom oysters, - Investigations for a specific technique of stock sampling for the subtidal culture, - Setting-up of the project co-management. L'année 2007, faisant suite à de fortes mortalités d'huîtres creuses (Crassostrea gigas) en baie de Quiberon (élevage au sol en eau profonde), a été l'année de gestation du projet RISCO-QB (Risques Conchylicoles en baie de Quiberon). Des discussions avec les différents partenaires potentiels ont eu lieu tout au long de l'année 2007 pour aboutir à la rédaction quasi-définitive du projet début 2008 qui vise 3 objectifs principaux : - l'estimation de la capacité trophique de la baie et l'adaptation de la biomasse en élevage, - l'impact du sédiment sur l'élevage au sol et l'adaptation des pratiques d'élevage, - l'évaluation de l'impact de ces 2 facteurs (trophique ...